Collisional shock waves induced by laser radiation pressure. (11th July 2019) - Henis, Zohar; Eliezer, Shalom; Raicher, Erez
Abstract: The formation of a collisional shock wave by the light pressure of a short-laser pulse at intensities in the range of 10 18 –10 23 W/cm 2 is considered. In this regime the thermodynamic parameters of the equilibrium states, before and after the shock transition, are related to the relativistic Rankine–Hugoniot equations. The electron and ion temperatures associated with these shock waves are calculated. It is shown that if the time scale of energy dissipation is shorter than the laser pulse duration a collisional shock is formed. The electrons and the ions in the shock-heated layer may have equal or different temperatures, depending on the laser pulse duration, the material density and the laser intensity. This shock wave may serve as a heating mechanism in a fast ignition scheme.